Effective Strain of BFRP for Confined Heat-Damaged Concrete Cylinders - Ouyang, Li-Jun; Wei, Xiao-Xiao; Ding, Bin; Gao, Wan-Yang (Frontiers in Materials, 2021)
It is widely accepted that concrete columns confined with fiber-reinforced polymer (FRP) jackets exhibit significant increases in strength and ductility with reference to the unconfined case. Existing experimental studies have indicated that the hoop rupture strains measured in the FRP jackets are significantly lower than the material strain capacity determined by the flat coupon tensile tests. A FRP efficiency factor is then usually used to define the ratio of the average hoop rupture strain to the material strain capacity of the FRP jackets, which governs the lateral FRP confinement as well as the peak strength and ultimate strain of the FRP-confined concrete under axial compression. FRP jackets are also expected to be a promising solution to repair damaged RC columns after fire exposure. However, there is lacking research on the behavior of FRP-confined fire or heat-damaged concrete columns. In particular, the FRP efficiency factor of FRP-confined fire or heat-damaged concrete columns has not yet been established. The paper presents the results of an experimental study aimed to investigate the effects of the historical high temperature and the layer of basalt FRP (BFRP) jackets on the efficiency factor of BFRP for the confined heat-damaged concrete cylinders. A sum of 51 standard concrete cylinders is prepared and tested under axial compression. The parameters varied between tests are the historical high temperature (20 °C, 200 °C, 400 °C, 600 °C or 800 °C) that is used to produce the heat damage of concrete cylinders and the number of layers of BFRP jackets (0, 2, 3 or 4). The test results have indicated that the efficiency factor of BFRP jackets increases with the historical high temperature but decreases slightly with the increase in the BFRP layers. A new temperature-dependent design equation for the BFRP efficiency factor of the confined heat-damaged concrete is proposed to consider the effects of the parameters mentioned above and can be used for practical design.